Who's who in the Ancient Near East - Leick, Gwendolyn, 1951- (Who's who series., 2002)
"Who was the author of the Gilgamesh epic? Who was the wealthiest businessman in Babylon? Who was the earliest known author in history? Which Hittite prince was meant to marry Tutankhamen's widow?" "These and many more questions are answered in this survey of the people who inhabited the Near East between the twenty-fifth and the second centuries BC. From Palestine to Iran, and from Alexander the Great to Zechariah, Who's Who in the Ancient Near East presents a unique and comprehensive reference guide for all those with an interest in the ancient history of the area. A full glossary, chronological chart, maps and bibliographical information complement the biographical entries."--Jacket